1999
DOI: 10.1103/physreva.59.4805
|View full text |Cite
|
Sign up to set email alerts
|

Electron-momentum densities of singly charged ions

Abstract: Spherically averaged electron momentum densities ⌸( p) are constructed by the numerical Hartree-Fock method for 54 singly charged atomic cations from He ϩ ͑atomic number Zϭ2) to Cs ϩ (Zϭ55) and 43 anions from H Ϫ (Zϭ1) to I Ϫ (Zϭ53) in their experimental ground state. As in the case of neutral atoms, the Hartree-Fock momentum densities for all these ions can be classified into three types; 28 cations and 10 anions have a unimodal density with a maximum at pϭ0, 22 cations and 21 anions have a unimodal density w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…25-27͒ atoms, explicit examination of the spherically-averaged h(u) and radial H(u) electron-pair intracule densities, where u denotes the relative distance between any pair of electrons, showed that the Fermi hole effect in high spin states appears only in a very small u region, and high spin states have a greater probability of finding a pair of electrons at smaller u than low spin states. The same has been confirmed recently 27 to be true for all the group 2 atoms up to Ra (Zϭ88), where Z stands for atomic number.…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…25-27͒ atoms, explicit examination of the spherically-averaged h(u) and radial H(u) electron-pair intracule densities, where u denotes the relative distance between any pair of electrons, showed that the Fermi hole effect in high spin states appears only in a very small u region, and high spin states have a greater probability of finding a pair of electrons at smaller u than low spin states. The same has been confirmed recently 27 to be true for all the group 2 atoms up to Ra (Zϭ88), where Z stands for atomic number.…”
Section: Introductionsupporting
confidence: 79%
“…In other words, a pair of electrons in a low energy state is more likely to be on opposite sides of the nucleus than in a high energy state, as observed for the 1 P Ϫ 3 P differences in the He atom 21 and the group 2 atoms. 27 This trend works to reduce the increase in the electron repulsion, observed in the analysis of intracule densities and moments, in a high energy state. The differences in the extracule moments ͗R k ͘ summarized in Table II are consistent with ⌬D(R); for all the five atoms, the moments ͗R k ͘ with k Ͼ0 increase while ͗R k ͘ with kϽ0 decrease in the order of the 3 P, 1 D, and 1 S states, with a sole exception for ͗R Ϫ2 ͘ of the C atom.…”
Section: A Group 14 Atomsmentioning
confidence: 97%
See 1 more Smart Citation
“…[29][30][31][32][33][34] There are many reasons which make the momentum space properties so attractive. One surely comes from the fact that many of them is accessible from measurements.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] T. Koga and coworkers have studied that according to ⌸(p) modalities the atoms that have been studied in this work can be separated into three distinct categories: 13,14 • Type A. Atoms with a unimodal ⌸(p) with its maximum located at the origin (p max ϭ0); i.e., a monotonically decreasing momentum density.…”
Section: Categories Of Reciprocal Form Factorsmentioning
confidence: 99%